La reconstrucción de todo lo deshecho: El proyecto intelectual tacneño en ‘Letras: Revista bimensual modernista’ - Quezada Morante, Valery (Pontificia Universidad Católica del Perú, 2025)
The emergence of Letras: A modernista bimonthly journal (1896-1898) must be understood within the historical context in which Tacna was under Chilean administration and awaiting the plebiscite that would determine either its definitive annexation to Chile or its reincorporation into Peru. It was published by the intellectual and diplomat José María Barreto. Letras articulated a dual project. It contributed to the development of Latin American modernismo while le-gitimizing Tacna’s role in the broader cultural life of Peru. The journal also assumed a patriotic role by constructing a community around love for the Peruvian homeland during Chilean occupation.

El surgimiento de Letras: Revista bimensual modernista (1896 - 1898) ocurre mientras Tacna está gobernada por Chile y a la espera del plebiscito que decidiría su anexión definitiva a dicho país o su reincorporación al Perú. Estuvo a cargo del intelectual y diplomático José María Barreto. Letras articuló un doble proyecto: contribuyó al modernismo latinoamericano mientras legitimaba el papel de Tacna en el desarrollo cultural del país; y, en el marco de la ocupación chilena, tuvo el rol patriótico de construir comunidad a partir del amor al Perú.
The reconstruction of everything undone: The Tacna intellectual project in ‘Letras: A bimonthly modernist magazine’
Keywords: Tacna; Literary journal; Captivity memory; Modernism; 19th century; Tacna; Revistas literarias; Memoria del cautiverio; Modernismo; Siglo XIX; https://purl.org/pe-repo/ocde/ford#6.00.00